Tuberculosis of Talus (Case Report) - Yılmaz, Erhan; Belhan, Oktay (Fırat University, 2002)
Most of the bone tuberculosis places in vertebral column. Foot and ankle tubercolusis is rare. At x-ray, talar cyst was observed in a 9 years-old child who came with left ankle pain since 5 months. Tuberculosis and Brucellosis tests were negatif. CRP was 6.3 mg/L. In MRI, talar lesion was evaluated as enfection. At histopathologic examination, chronic granulomatoz inflammation was observed. According to the ineffective chemotherapy and histopatholojic findings, case was diagnosed as bone Tuberculosis. Chemoterapy was applied for 1 year and clinical and radiological recovery were observed. We decided that, chemotherapy is sufficient in bone tuberculosis, but surgery may be neccessery in resistance cases.

Kas iskelet sistemi tüberkülozu olgularının büyük çoğunluğu omurgada görülür. Ayak ve ayak bileğinin tüberkülozu ise sık değildir. 9 yaşında, 5 aydan beri sol ayak bileği ağrısı, topallama ve şişlik şikayeti olan erkek çocuğun direk grafisinde kistik alan saptandı. PPD ve Brucella negatif, ESR 26 mm/saat, CRP 6.3 mg/L idi. Çekilen MRI'da talustaki kistik lezyonun enfeksiyon olabileceği düşünüldü. Biopsi materyalinin histopatolojik incelenmesi kronik granülomatöz iltihap lehine yorumlandı. Hastanın daha önceki uzun antibiyotik tedavisine cevapsız olması ve histopatolojik bulgulara dayanılarak tüberküloz tanısı konuldu. Hastaya 1 yıl süre ile antitüberküloz kemoterapi uygulandı. 1 yıl sonra radyolojik ve klinik düzelme bulguları görüldü. Kemik tüberkülozu olgularında kemoterapinin yeterli olduğu ancak dirençli olgularda cerrahi gerektiği kanısına varıldı.
Talus Tüberkülozu (Olgu Sunumu)